Genetic polymorphisms of metabolic enzyme genes associated with leukocyte mitochondrial DNA copy number in PAHs exposure workers. Issue 4 (31st March 2021) - Li, Xinling; Duan, Xiaoran; Zhang, Hui; Ding, Mingcui; Wang, Yanbin; Yang, Yongli; Yao, Wu; Zhou, Xiaoshan; Wang, Wei
Abstract: Background: Polycyclic aromatic hydrocarbons (PAHs) exposure had been reported to be a risk factor of mtDNAcn in our early study. However, the effect of metabolic enzymes' genetic polymorphisms on mtDNAcn in PAHs‐Exposure workers has not been fully evaluated. Aim: The aim of the study was to explore the effect of metabolic enzymes' genetic polymorphisms on mtDNAcn in PAHs‐Exposure. Methods and Results: We investigated the effects of metabolic enzymes' genetic polymorphisms on mtDNAcn among 544 coke oven workers and 238 office staffs. The mtDNAcn of peripheral blood leukocytes was measured using the Real‐time quantitative polymerase chain reaction (PCR) method. PCR and restriction fragment length was used to detect five polymorphisms in GSTT1, GSTM1, GSTP1 rs1695, CYP2E1 rs6413432, and CYP2E1 rs3813867. The mtDNAcn in peripheral blood leukocytes was significantly lower in the exposure group than that in the control group ( p < .001). The 1‐OHPYR had an increasing trend with the genotypes AA→AG → GG of GSTP1 rs1695 in the control group. Generalized linear model indicated that the influencing factors of mtDNAcn were PAHs‐exposure [ β (95% CI) = −0.420 (−0.469, −0.372), p < .001], male [ β (95% CI) = −0.058 (−0.103, −0.012), p = .013], and AA genotype for GSTP1 rs1695 [ β (95% CI) = −0.051 (−0.095, −0.008), p = .020]. Conclusion: The individuals carrying the AA genotype of GSTP1 rs1695 may have a lower mtDNAcn due to their weaker detoxification of PAHs.